Dudika, Negvar: Two German Anthroponyms in Texts from Novgorod - Nazarenko, Alexander V. (Slověne, 2015)
According to the Novgorod First Chronicle (in entries from 1055 and 1058), a servant (xolopъ) and probably steward (tiunъ) of the Novgorodian bishop Luka had the name Dudika. The name seems to be of Lower German origin (< Old Saxon Dōdico), and so Dudika himself must have been a Saxon. That is why, after he was convicted of calumniating his bishop, he fled to Germany (v Němci). A person named Negvar is mentioned in the year 1200 in the pilgrimage book of Antonius, archbishop of Novgorod, as a member of an embassy to Constantinople, which was directed by Roman Mstislavich, duke of Galich. This name can be interpreted as an Old Russian version of the Old Nordic Ingvarr. As a result of metathesis in the muta cum liquida group, after the pattern of the Slavic *orb- > old Russian rob-, a virtual form like the Old Russian *Nigvarъ might have appeared. The further transformation *Nigvarъ > Negvar was induced by frequent personal name models either with the initial group Ne- (such as Nedanъ, Nevidъ) or with the first stem Něg- (such as Něgoradъ). So the Old Scandinavian Ingvarr was reflected as a loan-name in the Old Russian dialects three times: Igorь (before losing the nasal vowels), Inъgvarъ, and Negvarъ (before and after losing the reduced vowels in unaccented positions).